Effectiveness of Subliminal Messages and Their Influence on People’s Choices - Rania Karam; Mohamad Abou Haidar; Abbas Khawaja; Ghida Al Laziki (European Scientific Journal, ESJ, 2017)
This article provides definitions for the conscious and subconscious minds, and shows their relation with the subliminal messages which are also defined. The subliminal CD’s, the way they function, and how they are recorded are explained in details. In addition, an interview with an expert in subliminal messages was conducted to enrich the article with more technical details. Moreover, the main objective of the research study was to show the effectiveness of the subliminal messages, and therefore to prove the influence they have on people’s choices in the auditory system. For this purpose, two experiments were carried out. The results proved that the experimental hypothesis is true: subliminal messages affect and influence the participants’ choice.